NUMERICAL INVESTIGATIONS OF INSTABILITIES IN GAS-SOLID FLUIDIZED BEDS - Das, Shyam Sumanta; Sobral, Yuri Dumaresq; Cunha, Francisco Ricardo da (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
A gas-solid fluidized bed consists of mixture of gas-solid in which the particles were suspended by an imposed upward flow. In the present paper, we have carried out two dimensional numerical simulations of gas-solid fluidized bed. CFD-DEM (Computational fluid dynamics-discrete element modeling) approach is used to model two phase flow composed of solid particles and gas inside the fluidized bed. It uses Eulerian and Lagrangian methods to solve fluid and solid particles respectively. Numerical simulations were carried out for various inlet gas velocities. The aim of the present work to investigate the instabilities associated with the fluidized bed. Spectral analyses were carried out to investigate the nature of the signals. The appearance of the bubble kind structure in the fluidized bed within few seconds of injection of gas shows the occurrence of instability in the fluidized bed system. This instability give rise to the formation bubbles of different sizes.